(untitled) (Journal Of Educational and Psychological Researches, 2010)
At the present time, human lives in a changable world. Complexity of life effects human who became unable to achieve his goals. For him, goals are no longer able to provide him with calm and psychological safty. Anxiety about indefinite future and any changes which transend his ablity to cooperate with affeets his life in general aspeets. All these things bring him a very sever tention, then he becomes extremace in his cooperation with these situations. He tends to live a lone in order to be a way from sequenees of changes. Starting from this urgent point, future compnses the core in youth’s life, then so many theories and studies affirm this point, and the necessity for mahing scientific studies appear to in cover the effect of these changes on the most important Layer in society which is young people . The research aimes at: • Measuring the level of anxiety towards future in young people . • Measuring the level of anxiety towards future in young people allording to sort (female, male), social status (married, single), job (student, employer) and age (18-24) and (25-30). For practical side, the research is limted to a sample of young people whose age (18-30) years old. For theoritical side, the researcher presents theories that are related to the present study are the earilier studies. To achieve the goals of this research, the researcher depends on anxiety toward future scale which is presented by (Masu’d,2006). This scale shows high validity and stability has got a constant (97.0) by using retesting and (71.0) by using the method of alpha and (78.0) by using split-half. The high stability of the scale proves its applicability for use. The sample of the theortical research consists of (151 young) female and male. The tools of the present research are represented by anxity future scale which is applied on the members of the sample. The data is treated satistically by using T-test for one specimen and T.test foe two specimen. The findings of the invistigation show that: • The sample shows anxity towards future. • There are statistical differences allording to social status (married, single) at single young. • There are no notable statistical diffrences allording to jobs (students, employers). In the light of the findings, the researcher present the following recommendations, provide young people with full a wareness about their future throughout letting them be a ware of their real ablities and helping them with planning skills. The researcher suggests applying another types of research about other psychological variables such as psychological pressure, in conscious ideas, psychological health.